Preliminary Evaluation of the Safety and Immunogenicity of an Antimalarial Vaccine Candidate Modified Peptide (IMPIPS) Mixture in a Murine Model (2019)
Malaria continues being a high-impact disease regarding public health worldwide; the WHO report for malaria in 2018 estimated that 219 million cases occurred in 2017, mostly caused by the parasite Plasmodium falciparum. The disease cost the lives of more than 400,000 people, mainly in Africa. In spite of great efforts aimed at developing better prevention (i.e., a highly effective vaccine), diagnosis, and treatment methods for malaria, no efficient solution to this disease has been advanced to date. The Fundación Instituto de Inmunología de Colombia (FIDIC) has been developing studies aimed at furthering the search for vaccine candidates for controlling P. falciparum malaria. However, vaccine development involves safety and immunogenicity studies regarding their formulation in animal models before proceeding to clinical studies. The present work has thus been aimed at evaluating the safety and immunogenicity of a mixture of 23 chemically synthesised, modified peptides (immune protection-inducing protein structure (IMPIPS)) derived from different P. falciparum proteins. Single and repeat dose assays were thus used with male and female BALB/c mice which were immunised with the IMPIPS mixture. It was found that single and repeat dose immunisation with the IMPIPS mixture was safe, both locally and systemically. It was observed that the antibodies so stimulated recognised the parasite's native proteins and inhibited merozoite invasion of red blood cells in vitro when evaluating the humoral immune response induced by the IMPIPS mixture. Such results suggested that the IMPIPS peptide mixture could be a safe candidate to be tested during the next stage involved in developing an antimalarial vaccine, evaluating local safety, immunogenicity, and protection in a nonhuman primate model. © 2019 Jennifer Lambraño et al.